P-69 Review of deaths occurring withing 48 hours of ED attendance, following the second wave of the COVID-19 pandemic. (20th March 2022) - Webster, Sarah; Tredgett, Kate
Abstract : Introduction: This review of patients who died rapidly after Emergency Department (ED) presentation, explores whether attendances were avoidable, and if so, how the pathway to attendance could be interrupted. Method: 22 consecutive patients who died within 48 hours of ED presentation in early 2021 were included. Data was collected from Primary Care records, ED and hospital notes. The patients' attendances were categorised as 'Unavoidable', 'Borderline', or 'Avoidable'. Demographics were compared and the Borderline and Avoidable attendances examined in detail. Results: Most attendances (59%) were Unavoidable, 23% Borderline, and the minority Avoidable (18%). Median age and frailty scores were highest in the Avoidable and lowest in the Unavoidable categories. In Borderline and Avoidable groups: Advance Care Plans (ACP) were completed pre-admission with wishes to die at home in 1/5 Borderline, and 4/4 Avoidable, cases. RESPECT forms completed in 77%. Dying was only identified pre-attendance in 2 patients – both categorised as Avoidable. One patient was conveyed because care could not be sourced quickly enough and one because despite care the family felt unable to cope. The remainder were admitted due to possible reversibility of and/or unexpected nature of deterioration. ACP was not completed in 3/5 Borderline cases, despite opportunities, but may have prevented admission in just one. 55% of patients had only virtual assessments from GP/Community Palliative Care prior to conveyance to hospital. Discussion: Most attendances were Unavoidable. For patients dying in the community, timely availability of adequate support is important to enable people to remain at home. ACP and RESPECT forms were often available but did not prevent admissions when it was not apparent the patient's deterioration represented a terminal event, highlighting the importance of senior clinician availability in the community. Further understanding of the impact of virtual working on clinical decision making, particularly for patients wishing to die at home.